Impact of Career Development on Employee Work Engagement: Study of Executive Employees of a Selected Apparel Organization in Colombo District, Sri Lanka - Fernando, B. B. D. R.; Pieris, M. D. P. (Department of of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka, 2021)
The impact of career development on employees’ work engagement has become a unique topic, which inspire to study much deeper. The general objective of the study was to find out the impact of career development on work engagement of executive level employees in a selected apparel organization in Colombo district, Sri Lanka. Sub objective of the study was to find out, whether availability of career development opportunities impact on work engagement, whether perceived supervisory support impact on work engagement and whether career identity impact on work engagement. To identify the relationship and impact of the study, correlation and simple regression analyses were employed by the researcher. Five Point Likert Scale was used to examine the respondent’s rule. The sample of the study was 77 executive employees of a selected apparel organization in Colombo district, Sri Lanka. And sample was randomly selected. Data interpretation and analyses was conducted by using the statistical package (SPSS 26.0), to find out the mean, mode, variance, standard deviation, correlation and regression analyses. Major finding of the study was indicated that, there is a positive impact of career development on work engagement of executive level employees in the selected apparel organization in Colombo district. Sri Lanka.
Keywords: Career Development, Employee Work Engagement